2002
DOI: 10.1017/s0016774600022678
|View full text |Cite
|
Sign up to set email alerts
|

Fluvial deposits as a record for Late Quaternary neotectonic activity in the Rhine-Meuse delta, The Netherlands

Abstract: Neotectonic movements have caused differential subsidence in the Lower Rhine Embayment during the Quaternary. The Late Weichselian and Holocene Rhine-Meuse fluvial archive in the central Netherlands was used to quantify neotectonic movements in a setting that was primarily controlled by sea-level rise and climate change. Evidence for neotectonic activity in the central Netherlands is reviewed. Sedimentary evidence shows that fluvial deposits of Late Weichselian and Holocene Rhine and Meuse (Maas) distributarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 31 publications
(46 reference statements)
3
62
0
Order By: Relevance
“…This is a remarkable difference with other large Allerød meandering systems in northwestern Europe (e.g. the Meuse valley (Huisink, 1998) and downstream continuations of Rhine and Meuse in the central Netherlands (Cohen et al, 2002), which are found in relative incised position). The Allerød meander belt in the Niers-Rhine course, carrying a minor proportion of the Rhine discharge at the time, as did the Wolfstrang system of the Oude IJssel course, also shows no floodplain incision.…”
Section: Late Pleniglacial Bølling and Older Dryasmentioning
confidence: 57%
See 2 more Smart Citations
“…This is a remarkable difference with other large Allerød meandering systems in northwestern Europe (e.g. the Meuse valley (Huisink, 1998) and downstream continuations of Rhine and Meuse in the central Netherlands (Cohen et al, 2002), which are found in relative incised position). The Allerød meander belt in the Niers-Rhine course, carrying a minor proportion of the Rhine discharge at the time, as did the Wolfstrang system of the Oude IJssel course, also shows no floodplain incision.…”
Section: Late Pleniglacial Bølling and Older Dryasmentioning
confidence: 57%
“…The Oude IJssel valley has formed as the product of deglaciation in the Saalian (Thomé, 1959;Van de Meene & Zagwijn, 1978;Klostermann, 1992;Busschers et al, 2008). The valley is located in the hinge zone area of the North Sea Basin (Cohen et al, 2002), on a relative stable block on the very northeastern edge of the Roer Valley Graben Rift System (Van Balen et al, 2005), the tectonic structure that hosts the Lower Rhine Embayment (Boenigk & Frechen, 2006). (Central Rhine, Niers-Rhine and Oude IJssel-Rhine) in the apex of the Erkens et al, 2011).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Wallinga (2001) showed that quartz OSL-dating is a useful tool for dating Late Glacial and Holocene Rhine-Meuse deposits. For a detailed description of the principles of OSLdating and its application to fluvial stratigraphy, we refer to Wallinga (2001) (Jelgersma, 1979;Van de Plassche, 1982); b. longitudinal section through the fluvio-deltaic wedge of the Holocene Rhine-Meuse delta with paleo-groundwater gradient lines (after Van Dijk et al, 1991;Cohen et al, 2002); and c. upstream migration of the aggradationincision boundary during the Holocene (after Cohen et al, 2002 . All ages in cal yr BP.…”
Section: And Osl-datingmentioning
confidence: 99%
“…The combined predictive power of the index-point data set and enveloping surfaces is in combining vertical resolution and lateral coverage. In the coastal prism (and in the paleovalley), paleogroundwater surfaces are generally smooth and only gently sloping, apart from local deformations due to differential subsidence (Cohen et al, 2002). Therefore, the application of groundwaterlevel age-depth relations over large distances is justified.…”
Section: Paleo-groundwater-level Data: Predictive Qualitymentioning
confidence: 99%